Emerging role of SUMOylation in plant development - Xu, Panglian (Landes Bioscience, 2013)
Post-translational attachment of small ubiquitin-like modifier (SUMO), defined as SUMOylation, has emerged as a new mechanism of protein regulation in plant biology. In plant, SUMOylation has been shown to play crucial roles in a variety of biotic and abiotic stress responses. Recent work using viable mutants with defective SUMOylation have indicated an important role for SUMOylation in a wide range of developmental processes, such as cell division, expansion, survival and differentiation, vegetative growth and reproductive development. This review will summarize the currently emerging information regarding the function of SUMOylation in plant development.